(untitled) (Journal of Family Sciences, 2017)
The final stage of life in the elderly experienced changes of physical, psychological, or social that can effect instability of self concept. The aim of this research was to analyzed the effect of cognitive function, social interaction to self concept of elderly widows and widowers. The location of this research in Timbulharjo village, Sewon sub-district, Bantul district, Yogyakarta who chosen purposively with the consideration of the region which have the most elderly. The sample of this research was the elderly people aged more than 60 years old that have been abandoned by partner of life during grater than or equal to 2 years a go. Sample total of this research were 30 elderly widows and 30 elderly widowers. This research showed that there were not difference of cognitive function and social interaction between of elderly widows and elderly widowers, however there was difference of self concept between of elderly widows and widowers. In addition, ages and education have correlation with cognitive function, and social interaction have correlation with self concept. Meanwhile, marital status have negative influence and social interaction have positive influence to self concept so that widows status can decrease self concept of elderly, and better social interaction than better of self concept of elderly.